The versatility of passivating carrier‐selective silicon thin films for diverse high‐efficiency screen‐printed heterojunction‐based solar cells. (12th December 2019) - Descoeudres, Antoine; Horzel, Jörg; Paviet‐Salomon, Bertrand; Senaud, Laurie‐Lou; Christmann, Gabriel; Geissbühler, Jonas; Wyss, Patrick; Badel, Nicolas; Schüttauf, Jan‐Willem; Zhao, Jun; Allebé, Christophe; Faes, Antonin; et al.
Abstract: Providing state‐of‐the‐art surface passivation and the required carrier selectivity for both contacts, hydrogenated amorphous silicon thin films are the key components of silicon heterojunction (SHJ) solar cells. After intensive optimization of these layers for standard front and back contacted (FBC) n ‐type cells, high surface passivation levels were achieved on cell precursors, demonstrated by minority carrier lifetimes exceeding 18 ms on float‐zone (FZ) and 11 ms on Czochralski (Cz) c‐Si wafers. The application of these very same layers on cheaper and commercially available Cz p ‐type wafers resulted in similar passivation quality, with lifetimes above 10 ms as well. Large‐area industrial bifacial FBC SHJ cells processed on wafers taken along the full length of a high‐resistivity Cz p ‐type ingot showed efficiencies in the 22.5% to 23% range, significantly higher than previously reported results on such substrates and on par with their n ‐type counterparts. Best efficiencies on large‐area monofacial devices (>220 cm 2 ) are 23.6% on Cz p ‐type and 24.4% on Cz n ‐type, similar to certified results obtained on lab‐scale cells (4 cm 2 ), 23.76% on FZ p ‐type and 24.21% on FZ n ‐type. Notably, no specific adaptation of the reference n ‐type cell process was necessary to achieve these results on p ‐type material. Additionally, a 25% certified efficiency has been obtained on medium‐sized (25 cm 2 ) interdigitated back‐contacted SHJ cells, featuring the same passivation layers developed for FBC devices. These results illustrate the versatility of the SHJ technology for various high‐efficiency screen‐printed solar cell configurations and show possible ways to improve its competitiveness on the global photovoltaic market. Abstract : We report that a full silicon heterojunction (SHJ) cell process optimized for n ‐type substrates can also be applied to p ‐type ones without any specific adaptation, keeping a high performance level (up to 23.6% on Cz p ‐type and 24.4% on Cz n ‐type). In addition, a certified efficiency of 25% has been obtained on IBC SHJ cells, featuring the same passivation layers developed for standard devices. These results illustrate the versatility of the SHJ technology for various high‐efficiency screen‐printed solar cell configurations.